Potential, Effectiveness, And Contribution Of Food And Beverage Tax Revenue In Increasing Local Revenue (PAD): An Empirical Study In Palu City 2019-2024 - Siti Fatimah; Selmita Paranoan; Chalarce Totanan; Ni Made Suwitri Parwati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the potential, effectiveness, and contribution of food and beverage taxes to the Local Own-Source Revenue (PAD) of Palu City for the period 2019–2024. Food and beverage taxes are an important source of revenue that reflects the level of community participation in regional development. This study uses a quantitative method with a descriptive approach, utilizing primary and secondary data from the Regional Revenue Agency (BAPENDA) and the Regional Financial and Asset Management Agency (BPKAD) of Palu City. The results show that the potential of food and beverage tax in Palu City reaches IDR 78,558,585,000, with the largest contribution coming from the restaurant and eatery sector. The effectiveness of tax collection in 2019–2023 was classified as highly effective, but declined dramatically in 2024 to ineffective. Although tax revenue realization increased every year, its contribution to PAD was still very low, at less than 1%. These findings emphasize the need for strategies to optimize tax collection, improve taxpayer compliance, and innovate in local tax management so that the potential of food and beverage taxes can be maximized to support local fiscal independence.